INVENTARISASI DAN IDENTIFIKASI SUMBER PENCEMAR AIR DI KOTA BANJARMASIN - Aditya Rahman; Muhammad Syahirul Alim; Umi Baroro Lili Utami (Universitas Lambung Mangkurat, 2011)
Wastewater sources in Banjarmasin include institutional sources consisting of industrial activities, hotels, hospitals, and domestic wastewater. To the present, the amounts of pollutant load, type of source water contaminants in Banjarmasin are not yet inventored and properly identified. The purpose of this study was to inventory and identification of pollutant sources of water in an attempt to control water pollution in Banjarmasin. The research methods refer to Permen LH no.01 of 2010 on the governance of water pollution control. Based on the governor's quality standards. No. 36 of 2008 of South Kalimantan, the study showed the greatest pollutant load of liquid waste was generated by restaurants, followed by hotels and hospitals. As for the river, when viewed based on BOD and DO, river water in Banjarmasin at each sampling points showed the river water quality was in the level of class III - IV. The study also showed that Load of pollutants in the waters of the river in Banjarmasin has exceeded the value of Pollutant Load capacity.